Incorporating local nature-based cultural values into biodiversity No Net Loss strategies. (April 2020) - Griffiths, Victoria F.; Bull, Joseph W.; Baker, Julia; Infield, Mark; Roe, Dilys; Nalwanga, Dianah; Byaruhanga, Achilles; Milner-Gulland, E.J.
Highlights: Cultural heritage is central to people's wellbeing in areas altered by development. It's importance to wellbeing revealed geographical and socio-demographic variation. Compensation may be unfeasible as natural sites of high spiritual value are unique. Not accounting for cultural heritage in NNL strategies can undermine wellbeing. Considering cultural values assists with designing more equitable NNL strategies. Abstract: Achieving "No Net Loss" (NNL) of nature from a development typically requires projects to follow a 'mitigation hierarchy', by which biodiversity losses are first avoided wherever possible, then minimised or remediated, and finally any residual impacts offset by conservation activities elsewhere. Biodiversity NNL can significantly affect people, including their cultural values. However, empirical research is lacking on how to incorporate impacts on cultural values of nature into NNL strategies. We use the Bujagali and Isimba Hydropower Projects and Kalagala Offset in Uganda as a case study to explore local people's perceptions of the importance of cultural heritage to their wellbeing, how the developments affected their cultural heritage, and how these perceived impacts could be incorporated into NNL strategies. We sampled six villages experiencing different levels of hydropower development along the Victoria Nile River. Many river features, particularly rapids and waterfalls, are important cultural sites, associated with spirits and are worshipped by local communities. Spiritual beliefs, rituals and ceremonies, nature, and how cultural heritage is changing were frequently mentioned when respondents described cultural heritage. People perceived cultural heritage to be an important component of their wellbeing, but its importance differed between villages and socio-demographic groups. Men and the less poor found it to be very important, whilst people who had lived in the village for a short time and who had higher education levels found it less important. Respondents in villages where sacred sites are well-known or still intact described cultural heritage as being an important factor contributing to wellbeing. The study highlights the complex relationships between cultural heritage, nature and people's wellbeing, and how essential it is to understand and account for cultural heritage when planning developments and associated offsets, if they are to be sustainable and fair to local people.